Global Distribution of Extended Spectrum Cephalosporin and Carbapenem Resistance and Associated Resistance Markers in Escherichia coli of Swine Origin – A Systematic Review and Meta-Analysis - Hayer, Shivdeep Singh; Casanova-Higes, Alejandro; Paladino, Eliana; Elnekave, Ehud; Nault, Andre; Johnson, Timothy; Bender, Jeff; Perez, Andres; Alvarez, Julio (Frontiers in Microbiology, 2022)
Third-generation cephalosporins and carbapenems are considered critically important antimicrobials in human medicine. Food animals such as swine can act as reservoirs of antimicrobial resistance (AMR) genes/ bacteria resistant to these antimicrobial classes, and potential dissemination of AMR genes or resistant bacteria from pigs to humans is an ongoing public health threat. The objectives of this systematic review and meta-analysis were to: 1) estimate global proportion and animal-level prevalence of swine E. coli phenotypically resistant to 3rd generation cephalosporins (3GCs) and carbapenems at a country level; and 2) measure abundances and global distribution of the genetic mechanisms that confer resistance to these antimicrobial classes in these E. coli isolates. Articles from four databases (CAB Abstracts, PubMed/MEDLINE, PubAg and Web of Science) were screened to extract relevant data. Overall, proportion of E. coli resistant to 3GCs was lower in Australia, Europe and North America compared to Asian countries. Globally, <5% of all E. coli were carbapenem-resistant. Fecal carriage rates (animal-level prevalence) were consistently manifold higher as compared to pooled proportion of resistance in E. coli isolates. blaCTX-M were the most common 3GC resistance genes globally, with the exception of North America where blaCMY were the predominant 3GC resistance genes. There was not a single dominant blaCTX-M gene subtype globally and several blaCTX-M subtypes were dominant depending on the continent. A wide variety of carbapenem-resistance genes (blaNDM-, VIM-, IMP-, OXA-48, KPC-) were identified to be circulating in pig populations globally, albeit at very-low frequencies. However, great statistical heterogeneity and a critical lack of metadata hinders the true estimation of prevalence of phenotypic and genotypic resistance to these antimicrobials. Comparatively frequent occurrence of 3GC resistance and emergence of carbapenem resistance in certain countries underline the urgent need for improved AMR surveillance in swine production systems in these countries.